2019
DOI: 10.1002/jcp.28539
|View full text |Cite
|
Sign up to set email alerts
|

Dexmedetomidine ameliorates lipopolysaccharide‐induced acute kidney injury in rats by inhibiting inflammation and oxidative stress via the GSK‐3β/Nrf2 signaling pathway

Abstract: Acute kidney injury (AKI) is a frequent and serious complication of sepsis; however, there are currently no effective therapies. Inflammation and oxidative stress are the major mechanisms implicated in lipopolysaccharide (LPS)‐induced AKI. Dexmedetomidine (DEX) has been reported to have remarkable anti‐inflammatory and antioxidant effects. Here, we examined the renoprotective effects of DEX and potential underlying mechanisms in rats with LPS‐induced AKI. We analyzed renal function and structure; serum inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 78 publications
(64 citation statements)
references
References 77 publications
5
57
0
Order By: Relevance
“…We have confirmed that DEX protects against LPS-induced AKI via anti-inflammatory and anti-oxidative mechanisms (Chen et al, 2019;Feng et al, 2019;Yao et al, 2019). Also, we found that DEX regulated renal autophagy, a phenomenon that was accompanied by the amelioration of oxidative stress and cell apoptosis.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…We have confirmed that DEX protects against LPS-induced AKI via anti-inflammatory and anti-oxidative mechanisms (Chen et al, 2019;Feng et al, 2019;Yao et al, 2019). Also, we found that DEX regulated renal autophagy, a phenomenon that was accompanied by the amelioration of oxidative stress and cell apoptosis.…”
Section: Discussionsupporting
confidence: 70%
“…LPS, a known toxic component of Gram-negative bacteria, is widely used to induce SAKI in animal models (Jou-Valencia et al, 2018), and studies have confirmed that the intraperitoneal administration of LPS for 4 h induces AKI (Chen et al, 2019;Feng et al, 2019). After LPS treatment, the indicators of kidney injury (BUN, Cre, KIM-1, and NGAL) are significantly increased, suggesting renal dysfunction and kidney injury.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Basic studies of the Nrf2 pathway have demonstrated multiple cytoprotective functions of Nrf2 and unveiled regulatory mechanisms of Nrf2 activity in response to oxidative stress. Recent studies have shown that activated Nrf2 in nuclei is degraded through βTrCP-mediated ubiquitination to avoid overactivation of Nrf2 [90,99,120], supporting the safety of chemical compounds activating Nrf2 for patients. Because oxidative stress is a primary factor for tissue damage in every organ, pharmacologically driving the antioxidative response system by Nrf2 activators is plausible for curing a variety of diseases.…”
Section: Conclusion and Perspectivementioning
confidence: 95%